Association between internet addiction and sleep quality in medical students: a longitudinal study - Guo, Chaowei; Chen, Ming; Ji, Xiaotong; Li, Jiang; Ma, Yi; Zang, Shuang (Frontiers in Psychology, 2025)
ObjectiveThe study aimed to confirm the hysteresis effect of internet addiction on sleep quality and examine the association between internet addiction and sleep quality among medical students from the first to the third academic year.MethodsA repeated measures observational cohort study was conducted, involving 667 medical students at China Medical University from 2017 to 2019. The Kruskal-Wallis test was used to analyze repeated measurement data, and cross-lagged panel models were employed to assess the associations between internet addiction and sleep quality within and across different time intervals.ResultsInternet addiction was significantly associated with sleep quality (p < 0.001). Notably, internet addiction in the first year was positively associated with sleep quality in the second year.ConclusionThis study underscores the importance of understanding the association between internet addiction and sleep quality as medical students progress through their academic years. Attention should be directed towards the long-term adverse effects of internet addiction on the future sleep quality of medical students.